The roles of XJ13 and XJ44-specific mutations within the Candid #1 GPC in Junin virus attenuation - Manning, John Tyler; Maruyama, Junki; Wanninger, Timothy; Reyna, Rachel A.; Stevenson, Heather L.; Peng, Bi-Hung; Mantlo, Emily K.; Huang, Cheng; Paessler, Slobodan (Frontiers in Immunology, 2023)
Junin virus (JUNV) is a member of the Arenaviridae family of viruses and is the pathogen responsible for causing Argentine hemorrhagic fever, a potentially lethal disease endemic to Argentina. A live attenuated vaccine for human use, called Candid#1, is approved only in Argentina. Candid#1 vaccine strain of Junin virus was obtained through serial passage in mouse brain tissues followed by passage in Fetal Rhesus macaque lung fibroblast (FRhL) cells. Previously, the mutations responsible for attenuation of this virus in Guinea pigs were mapped in the gene encoding for glycoprotein precursor (GPC) protein. The resulting Candid#1 glycoprotein complex has been shown to cause endoplasmic reticulum (ER) stress in vitro resulting in the degradation of the GPC. To evaluate the attenuating properties of specific mutations within GPC, we created recombinant viruses expressing GPC mutations specific to key Candid#1 passages and evaluated their pathogenicity in our outbred Hartley guinea pig model of Argentine hemorrhagic fever. Here, we provide evidence that early mutations in GPC obtained through serial passaging attenuate the visceral disease and increase immunogenicity in guinea pigs. Specific mutations acquired prior to the 13th mouse brain passage (XJ13) are responsible for attenuation of the visceral disease while having no impact on the neurovirulence of Junin virus. Additionally, our findings demonstrate that the mutation within an N-linked glycosylation motif, acquired prior to the 44th mouse brain passage (XJ44), is unstable but necessary for complete attenuation and enhanced immunogenicity of Candid#1 vaccine strain. The highly conserved N-linked glycosylation profiles of arenavirus glycoproteins could therefore be viable targets for designing attenuating viruses for vaccine development against other arenavirus-associated illnesses.